Genetic Characterization of Water Yam (Dioscorea alata L.) and Production Constraints of Yam in Pwani Region and Unguja Island, Tanzania - Temu, Gladness E; Mlegi, Veneranda E; Luambano, Nessie D (Tanzania Journal of Science, 2024)
Yam (Dioscorea spp.) is a tuber crop cultivated in over 30% of all regions in Tanzania, contributing to the carbohydrate needs of many households. The morphological and genetic diversity of water yam (D. alata L.) local cultivars collected from Pwani region and Unguja Island were evaluated using 26 agro-morphological characters and 10 Short Sequence Repeat (SSR) markers. Cluster analysis using morphological characters classified nine water yam local cultivars into two main clusters with three subclusters. Tuber flesh and leaf colour were the main descriptors for clustering. The genetic diversity of 128 water yam genotypes using ten polymorphic SSR markers generated a total of 40 alleles that ranged from 2 to 7 per SSR marker. The mean polymorphic information content (PIC) ranged from 0.3 to 0.9, with a mean of 0.56. Cluster analysis separated 128 yam genotypes into two main clusters with five subclusters. The findings revealed relatively high genetic diversity of D. alata in the study areas. A structured questionnaire revealed drought (29.3%) and lack of planting materials (23.3%) as the major constraints to yam production in the study areas. Information reported in this study is useful in improving, reviving and promoting yam through breeding and conservation programs.